Trapezius-sparing Approach to Osteochondromas on the Ventral Surface of the Scapula. Issue 3 (September 2018) - Stevens, Jarrad; Stirling, Paul; Patton, James T.
Abstract : Lesions affecting the ventral surface of the scapula are rare but can be associated with significant mechanical symptoms, such a pseudowinging or snapping scapula syndrome. Excision of osteochondromas arising from this region can be challenging due to the numerous muscle origins and attachments. Access to the bony surface of the scapula may be associated with extensive muscular detachment and soft tissue dissection. We describe a novel open trapezius-sparing approach to the ventral surface of the scapula.